Analisis Kemampuan Kinerja Keuangan Dalam Melaksanakan Otonomi Daerah Di Kabupaten Lombok Barat Periode 2018-2022 - Lina Ma’anur Rapika; I Made Murjana; Topan Siswanto (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This study aims to find out how the regional financial capacity is in the implementation of regional autonomy in West Lombok Regency. By using descriptive research methods, by using financial ratios, namely the ratio of independence, the ratio of effectiveness and efficiency ratio, activity ratio and growth ratio. The results showed that the results of the ratio of regional financial independence were indicated by ratios between 0-25% which belonged to an instructive relationship pattern where the role of the Central Government was still large, the level of independence of West Lombok Regency was not yet able to carry out regional autonomy. The effectiveness ratio shows that the realization of Regional Original Revenue has not exceeded the budget and the efficiency ratio in 2018 and 2019 is between 80-90% which is classified as quite efficient, in 2020 and 2021 the ratio is between 90-100% which is classified as less efficient and in 2022 the ratio figure is 100.48% which is classified as inefficient. The activity ratio shows the ratio between 60-80% which belongs to the compatible category. The growth ratio shows that from 2018 to 2019 the growth of Local Own Revenue increased by 13.92% which is relatively low, the growth of Local Own Revenue from 2019 to 2020 decreased by -11.36% which is very low, the growth of Regional Own Revenue from 2020 to 2021 it has increased by 34.63% which is classified as moderate and the growth of Local Own Revenue in 2021 towards 2022 has decreased by -8.85% which is very low.